2000
DOI: 10.4049/jimmunol.165.2.931
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptor 2 on γδ T Cells Bearing Invariant Vγ6/Vδ1 Induced byEscherichia coliInfection in Mice

Abstract: We recently reported that the number of γδ T cells was increased after infection with Escherichia coli in C3H/HeN mice. We here showed that an i.p. injection with native lipid A derived from E. coli induced an increase of γδ T cells in the peritoneal cavity of LPS-responsive C3H/HeN mice and, albeit to a lesser degree, also in LPS-hyporesponsive C3H/HeJ mice. The purified γδ T cells from C3H/HeN and C3H/HeJ mice expressed a canonical TCR repertoire encoded by Vγ6-Jγ1/Vδ1-Dδ2-Jδ2 gene segments and proliferated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
2
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 61 publications
2
128
2
1
Order By: Relevance
“…infection with E. coli (23)(24)(25)(26), we further examined the IL-17 production and neutrophil infiltration in V␦1 Ϫ/Ϫ mice. Although there was no difference in the number of ␥␦ T cells between naive V␦1 ϩ/Ϫ and V␦1 Ϫ/Ϫ mice, IL-17 production 6 h after i.p.…”
Section: ␥␦ T Cells Are Responsible For the Il-17 Production And Neutmentioning
confidence: 99%
See 1 more Smart Citation
“…infection with E. coli (23)(24)(25)(26), we further examined the IL-17 production and neutrophil infiltration in V␦1 Ϫ/Ϫ mice. Although there was no difference in the number of ␥␦ T cells between naive V␦1 ϩ/Ϫ and V␦1 Ϫ/Ϫ mice, IL-17 production 6 h after i.p.…”
Section: ␥␦ T Cells Are Responsible For the Il-17 Production And Neutmentioning
confidence: 99%
“…infection with Escherichia coli (23)(24)(25)(26). Although it is well established that neutrophils are essential in bacterial clearance, roles of IL-17 in this model are unknown.…”
mentioning
confidence: 99%
“…Preparation and adoptive transfer of TCR gd T cells TCR Vg6 + gd T cells were prepared from Escherichia coli (E. coli)-infected peritoneal cavity (PEC) cells as reported previously (21,22), because E. coli-induced peritoneal TCR gd T cells consist exclusively of TCR Vg6 + gd T cells (21,22) and express IL-17A (23). TCR Vg4 + gd T cells were obtained from the lung infected i.…”
Section: Histopathologymentioning
confidence: 99%
“…Also, though it is widely accepted that γδ T cells recognize microbial nonpeptidic phosphorylated molecules [16][17][18] and alkylamines [19,20] in a TCRdependent manner, LPS has not, to our knowledge, been described as a TCR ligand. While we have not precisely determined the mechanism of LPS detection, transcripts encoding many TLRs and other pattern recognition proteins are readily detected in γδ T cells [15,[21][22][23][24][25]. Other groups have shown that TLR agonists have co-stimulatory effects in combination with TCR engagement on γδ T cells, similar in many respects to the priming effect described here [21,25].…”
Section: Discussionmentioning
confidence: 58%